2016
DOI: 10.1111/jipb.12473
|View full text |Cite
|
Sign up to set email alerts
|

OsGRF4 controls grain shape, panicle length and seed shattering in rice

Abstract: Traits such as grain shape, panicle length and seed shattering, play important roles in grain yield and harvest. In this study, the cloning and functional analysis of PANICLE TRAITS 2 (PT2), a novel gene from the Indica rice Chuandali (CDL), is reported. PT2 is synonymous with Growth‐Regulating Factor 4 (OsGRF4), which encodes a growth‐regulating factor that positively regulates grain shape and panicle length and negatively regulates seed shattering. Higher expression of OsGRF4 is correlated with larger grain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 44 publications
6
109
0
4
Order By: Relevance
“…OsGRF4 , a target of miR396, reportedly regulates a CK dehydrogenase precursor gene and controls rice grain shape (Sun et al, 2016), while TCP14 and TCP15 TFs, which mediate CK responses, were found to cause excessive proliferation of the boundaries of the Arabidopsis gynoecium replum (Takei et al, 2001). Isopentenyl adenine (iPA) and zeatin riboside (ZR) are the major CK species in maize (Takei et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…OsGRF4 , a target of miR396, reportedly regulates a CK dehydrogenase precursor gene and controls rice grain shape (Sun et al, 2016), while TCP14 and TCP15 TFs, which mediate CK responses, were found to cause excessive proliferation of the boundaries of the Arabidopsis gynoecium replum (Takei et al, 2001). Isopentenyl adenine (iPA) and zeatin riboside (ZR) are the major CK species in maize (Takei et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Grain size and shape in rice are complex genetic traits, controlled by a large number of quantitative trait loci (QTLs). A number of regulatory genes have been identified through QTL mapping, including GW2, GS 3, BG1 , GW8, GW7 and GW5 (Zuo and Li ; Sun et al ; Li et al ; Xu et al ). For example, GW2 encodes an ortholog of Arabidopsis DA2 and controls seed size, via the ubiquitin‐proteasome pathway.…”
Section: Introductionmentioning
confidence: 99%
“…PL QTL is commonly co‐identified with heading date (Liu et al, ). Growth‐Regulating Factor 4 ( OsGRF4 ) controls synchronously PL, grain shape and seed shattering in rice by regulating two cytokinin dehydrogenase precursor genes ( CKX5 and CKX1 ) resulting in increased cytokinin level (Sun et al, ). Additionally, for the three major QTLs qPL10 , qSPP10 and qPH10 , their LOD confidence intervals mostly overlapped one another in the same interval between the markers RM1375 and RM3229 on chromosome 10, indicating that the locus in this interval might harbour a gene with pleiotropic effects on the traits of PH, PL and SPP (Kovi et al, ).…”
Section: Discussionmentioning
confidence: 99%